Prepregnancy and Early Pregnancy Calcium Supplementation Among Women at High Risk of Preeclampsia: A Multicenter, Double-blind, Randomized, Placebo-controlled Trial. Issue 3 (September 2019) - Hofmeyr, G.J.; Betrán, A.P.; Singata-Madliki, M.; Cormick, G.; Munjanja, S.P.; Fawcus, S.; Mose, S.; Hall, D.; Ciganda, A.; Seuc, A.H.; Lawrie, T.A.; Bergel, E.; et al.
Abstract : ( Lancet . 2019;393:330–339) Approximately 14% of maternal deaths worldwide are directly caused by hypertensive disorders of pregnancy, including preeclampsia. On the basis of surprisingly low rates of preeclampsia in low-income countries with high-calcium diets, it has been suggested that calcium deficiency may be linked to preeclampsia and several randomized controlled trials (RCTs) have tested the hypothesis that calcium supplementation may prevent preeclampsia. One study found reductions in the severity of preeclampsia, maternal morbidity and mortality and neonatal mortality, but no significant effect on preeclampsia prevalence. A meta-analysis of 13 RCTs found that calcium supplementation decreased preeclampsia rates by approximately half, but one limitation was small sample sizes of the studies included. This current study aimed to determine whether calcium supplementation before pregnancy and during the first half of pregnancy would reduce the development of preeclampsia in women who experienced preeclampsia or eclampsia in a previous pregnancy.